ANALISIS PENDAPATAN DAN KEUNTUNGAN USAHATANI KOPI DI DUSUN PUNIK KECAMATAN BATULANTEH - Rahim, Abdul; Lestari, Heni (Jurnal Ekonomi & Bisnis, 2024)
The purpose of this study was to know the income and profits of coffee farmers in Punik Hamlet, Batulante sub-district, Sumbawa district. The type of this study was quantitative descriptive study. The data used was primary data. The populations in this study were all coffee farmers in the Punik hamlet consisted of 100 populations. The sampling technique used was saturated samples, thus the number of samples in this research were 100. The method used to collect data were interviews and documentation. The data analysis tool is by using income analysis techniques. The results of this study showed that coffee farming carried out in Punik Hamlet, Batulanteh District has made a positive contribution to increasing community income and profits. The average income of coffee farmers in Punik Hamlet, Batu Lanteh District in one production is IDR 1,272,500/Ha/Farmer, while the average cost incurred by coffee farmers in one production is IDR 775,000/Ha/Farmer, so that the average profit obtained by coffee farmers in one production is IDR 497,000/Ha/Farmer. The profits obtained by farmers from the coffee sector are relatively small compared to other agricultural subsectors. Therefore, one of the efforts that can be made in order to increase the income of coffee farmer households is by increasing the added value of coffee commodities through further processing (agroindustry).